2019
DOI: 10.1021/acs.biomac.9b01016
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Changes in Lignin Following Polymerization and Its Effects on Flocculating Clay Particles

Abstract: Cationic kraft lignin (CKL) macromolecules were produced via polymerizing kraft lignin (KL) with [2-(acryloyloxy)ethyl]trimethylammonium chloride (ATAC) or [2-(methacryloyloxy)ethyl]trimethylammonium methyl sulfate (METAM). Despite slightly different charge densities (2.3−2.5 mmol/g) of CKL, lignin−METAM (KL−METAM) had a significantly larger molecular weight and radius of gyration. A correlation was observed between the structure of CKLs and their impacts on the surface hydrophilicity of kaolin particles. In i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…In this work, HL-METAC and HL-MAPTAC were produced following free radical polymerization (see the Supporting Information, Scheme S1). [7,17] As both CHL polymers had asymmetric molecular structures, the dipole moment (μ) vectors on each polymer cannot cancel each other creating polar molecules. As shown in Scheme 1, the larger electronegativity of the oxygen atom in the METAC structure of HL-METAC makes this macromolecule interact more with colloidal particles in an aqueous solution (i. e., electrostatic interactions).…”
Section: Structure Of Lignin Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…In this work, HL-METAC and HL-MAPTAC were produced following free radical polymerization (see the Supporting Information, Scheme S1). [7,17] As both CHL polymers had asymmetric molecular structures, the dipole moment (μ) vectors on each polymer cannot cancel each other creating polar molecules. As shown in Scheme 1, the larger electronegativity of the oxygen atom in the METAC structure of HL-METAC makes this macromolecule interact more with colloidal particles in an aqueous solution (i. e., electrostatic interactions).…”
Section: Structure Of Lignin Polymermentioning
confidence: 99%
“…Cationic hydrolysis lignin (CHL) was synthesized in a semi-dried condition based on the method developed in the previous work. [17] In this set of experiments, 2 g of HL was mixed with water to make a mixture of 60 wt % solid content. The polymerization reaction was performed at different reaction temperatures (70,80, and 90°C), times (1, 2, and 3 h), Na 2 S 2 O 8 dosages (0.75 wt % and 1.5 wt % based on lignin mass) and cationic monomer (METAC or MAPTAC)/lignin mole ratios (0.4, 0.8, 1.2, 1.6 and 2.4 mol mol À 1 ).…”
Section: Cationization Of Hydrolysis Ligninmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Structurally,l ignin is composed of both a hydrophobic skeleton (phenylpropanem onomers) and hydrophilic functional groups, such as carbonyl and phenolic hydroxy groups. [24,25] Lignin extractedi nt he pulp and paper industry was suggested to have potential for variousa pplications, such as bio-based adhesives, stabilizers, and nano-and microscale carriers by producing water-dispersed lignin nanoparticles. [26,27] For example, Wei et al [17] reported generating unmodified lignin particles by adjusting the pH value of aqueous lignin solutions from an alkaline system.…”
Section: Introductionmentioning
confidence: 99%
“…However, lignin is still considered as an underutilized material because only 1–2 % of its vast production annually (50–70 million tons) is utilized for the production of value‐added products . Structurally, lignin is composed of both a hydrophobic skeleton (phenylpropane monomers) and hydrophilic functional groups, such as carbonyl and phenolic hydroxy groups . Lignin extracted in the pulp and paper industry was suggested to have potential for various applications, such as bio‐based adhesives, stabilizers, and nano‐ and microscale carriers by producing water‐dispersed lignin nanoparticles .…”
Section: Introductionmentioning
confidence: 99%